2016
DOI: 10.1039/c6ra08247e
|View full text |Cite
|
Sign up to set email alerts
|

Photofixation of atmospheric nitrogen to ammonia with a novel ternary metal sulfide catalyst under visible light

Abstract: Light. -The new photocatalyst Mo 0.1Ni0.1Cd0.8S is prepared from aqueous solutions of (NH 4)2MoO4, Ni(NO3)2, Cd(OAc)2, and Na2S (autoclave, 160 C, 16 h). The material exhibits outstanding photofixation ability of atmospheric nitrogen to produce ammonia under visible light irradiation. The obtained catalyst is Mo and Ni co-doped CdS with many sulfur vacancies, which not only serve as active sites to adsorb and activate N 2 molecules but also promote charge transfer from the catalyst to N2 molecules. -(CAO, Y.;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…Compared to NiFeS NS, an obvious electron paramagnetic resonance (EPR) signal (g=2.003) was observed in NiFeS 1‐x UNM (Figure a), indicating the formation of sulfur vacancies . After deconvolution of XPS spectra, the ratios of Ni 2+ /Ni 3+ (Figure b) and Fe 2+ /Fe 3+ (Figure c) in NiFeS 1‐x UNM were both larger than those of NiFeS NS, revealing the existence of more sulfur vacancies along with more low‐valence metals in NiFeS 1‐x UNM .…”
Section: Figuresupporting
confidence: 85%
“…Compared to NiFeS NS, an obvious electron paramagnetic resonance (EPR) signal (g=2.003) was observed in NiFeS 1‐x UNM (Figure a), indicating the formation of sulfur vacancies . After deconvolution of XPS spectra, the ratios of Ni 2+ /Ni 3+ (Figure b) and Fe 2+ /Fe 3+ (Figure c) in NiFeS 1‐x UNM were both larger than those of NiFeS NS, revealing the existence of more sulfur vacancies along with more low‐valence metals in NiFeS 1‐x UNM .…”
Section: Figuresupporting
confidence: 85%
“…DFT calculations indicated that the large number of OVs on the nanosheet edge or surface formed a defect state lying in the middle of the bandgap, serving as electron-trapping sites that facilitated photo-induced charge transfer from LDH to N 2 . In addition, sulfur and nitrogen vacancies were also proposed to play a similar role as OVs in the nitrogen photofixation process, as exemplified by the ternary metal sulfides [124,125] and graphitic carbon nitride systems [126] .…”
Section: Photocatalytic Ammonia Synthesismentioning
confidence: 99%
“…In this regard, Hu's group continues to investigate the effect of different metal doping on ternary metal sulfide. Mo and Ni doped CdS can distort the crystal structure, leading to the formation of sulfur vacancies in obtained tri-component metal sulfide [72]. In order to compare the influence of sulfur vacancies, the as-prepared samples were calcined in O 2 gas to remove sulfur vacancies.…”
Section: Sulfur Vacanciesmentioning
confidence: 99%
“…Figure 16. (a) A schematic illustration the mechanism of Au-Os nanocomposite for NH3 photofixation [79]; (b) Schematic diagram of photochemical nitrogen reduction of Au/bSi/Cr [72]. (Reproduced with permission from the respective publishers).…”
Section: Plasmon Enhancementmentioning
confidence: 99%